Prevalence of depressive symptoms in elderly cancer patients receiving chemotherapy and influencing factors. Issue 5 (11th July 2018) - Atag, Elif; Mutlay, Feyza; Soysal, Pinar; Semiz, Huseyin S.; Kazaz, Seher N.; Keser, Murat; Ellidokuz, Hulya; Karaoglu, Aziz
Abstract : Background: Depression is one of the most prevalent causes of distress in the geriatric population. The purpose of this study was to examine the prevalence of depressive symptoms in elderly cancer patients and to determine the possible associated factors. Methods: Cancer patients 65 years or older and on active chemotherapy completed the Yesavage Geriatric Depression Scale. We examined the relationship of depressive symptoms with age, gender, marital status, educational background, type of cancer, stage of disease, comorbidities, types of treatment for cancer, the duration after diagnosis of cancer, social support, and pain status. Results: The study included 170 patients with a mean age of 71 years, and 47.1% were women. The prevalence of a high depressive symptom score was 19.4%. Of the patients who had a high depressive symptom score based on the Yesavage Geriatric Depression Scale, 18.2% had already been diagnosed with depression and used antidepressants. The mean pain score was significantly higher in patients who had a high depressive symptom score compared to others ( P  = 0.012). Conclusion: The prevalence of depressive symptoms in elderly cancer patients receiving chemotherapy was similar to that in the geriatric population without cancer. It was also consistent with previous studies on elderly cancer population. Pain was found to be a factor related to depressive symptoms. The prevalence of depression may be reduced by pain control. The treatment of depression may both improve the patient's quality of life and enhance their compliance with treatment.